Studies On Motile Aeromonas Spp. Associated With Healthy And Epizootic Ulcerative Syndrome-Positive Fish - Torres, James L. (1990)
Aeromonas hydrophila was reported to be associated with epizootic ulcerative syndrome ( EUS ) outbreaks in the Asia-Pacific region since the 1980 s. However , the precise role of A . hydrophila in EUS is not clear because its taxonomy is confusing , with reports of wide phenotypic , serological and genotypic character is tics of the organism . Aeromonas hydrophila is normally present in freshwater environments and in fish intestines . This study was , therefore , undertaken to examine the relation ships among motile Aeromonas spp. as sociated with healthy and EUS-positive fish .